FOREIGN POLICY IN POLITICAL-PARTISAN COMPETITION: POSITIONING OF PARLIAMENTARY ELITES IN ARGENTINA, BRAZIL, CHILE, PARAGUAY AND URUGUAY - Sendra, Mariana (Política. Revista de Ciencia Política, 2018)
The study of political elite opinion on foreign policy has been little developed in Latin America. This article aims to identify and describe the foreign policy positioning of the political parties with parliamentary representation in five Southern Cone countries - Argentina, Brazil, Chile, Paraguay and Uruguay - from an ideational perspective, that is, from the preferences of the legislators. Using data from the PELA (Parliamentary Elites of Latin America) of the University of Salamanca, a typology of political parties is built up according to their priority area of foreign policy, associated with orientations in models of economic regulation as well. The results show that while in Chile, Paraguay and Uruguay the foreign policy dimension does not divide political competition, in Argentina and Brazil differentiated positions are distinguished between the political parties.